Can including pros and cons increase the helpfulness and persuasiveness of online reviews? The interactive effects of ratings and arguments - Schlosser, Ann E. (Journal of Consumer Psychology, 2011)
AbstractOne guideline given to online reviewers is to acknowledge a product's pros and cons. Yet, I argue that presenting two sides is not always more helpful and can even be less persuasive than presenting one side. Specifically, the effects of two‐ versus one‐sided arguments depend on the perceived consistency between a reviewer's arguments and rating. Across a content analysis and three experiments that vary the information provided in the online review and whether the ratings are positive or negative, the results support these predictions. Furthermore, beliefs that the reviewer is able (vs. willing) to tell the truth mediated the effects.